Implicit knowledge of general upper secondary school in a bridge-building project. Issue 3 (1st September 2016) - Rasmussen, Annette; Andreasen, Karen
ABSTRACT: Bridge-building activities are practiced widely in the education systems of Europe. They are meant to bridge transitions between lower and upper secondary school and form a mandatory part of the youth guidance system in Denmark. By giving pupils the opportunity to experience the different educational context of upper secondary school, bridge-building activities are meant to facilitate their decision-making on educational paths, but also to attract more and new groups of pupils. However, the premises of the inherent differences of educational contexts and of pupils' lacking knowledge of upper secondary education can be questioned. In this ethnographic case study of a bridge-building project in a rural area in Denmark, we analyse the implicit knowledge of the general upper secondary school, as it is practiced in a bridge-building project, and how it is experienced by the pupils on the background of their prior knowledge . The analysis is theoretically informed by especially the code concepts of Basil Bernstein.